2011
DOI: 10.1016/j.jastp.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of small ion concentration near the Earth's surface

Abstract: a b s t r a c tAtmospheric ions produced by radon gas exhalation from the Earth's surface can play a vital role in the electrification of atmosphere, especially during nights when the gases are trapped in a stable layer close to the surface. The measurements of concentration of radon and its progeny, air conductivity and aerosol size distribution made at Pune, India, have been analyzed. The concentrations of radon and its progeny show maxima during night and early morning hours, between 0500 and 0700 IST when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…PECIA could not be associated with local traffic as the periods and timings of ion/aerosol particle concentration maxima generally preceded by 2–3 h the peak traffic hours, which were ∼0900–1100 LT at this location. Earlier observations of enhancement of ions and conductivity (Dhanorkar and Kamra, ) and radon concentrations (Kamsali et al , ) observed at the Atmospheric Electricity Observatory,∼100 m away from this site, were also reported during the same period. Such enhancements of ions and aerosol particles can be associated with accumulations of ions, aerosols, radioactive decay products and precursor gases below inversion layers at night‐time (Porstendörfer, ) and their downward transport with the ketabatic winds along the surrounding hill‐slopes in the morning.…”
Section: Observationssupporting
confidence: 75%
See 2 more Smart Citations
“…PECIA could not be associated with local traffic as the periods and timings of ion/aerosol particle concentration maxima generally preceded by 2–3 h the peak traffic hours, which were ∼0900–1100 LT at this location. Earlier observations of enhancement of ions and conductivity (Dhanorkar and Kamra, ) and radon concentrations (Kamsali et al , ) observed at the Atmospheric Electricity Observatory,∼100 m away from this site, were also reported during the same period. Such enhancements of ions and aerosol particles can be associated with accumulations of ions, aerosols, radioactive decay products and precursor gases below inversion layers at night‐time (Porstendörfer, ) and their downward transport with the ketabatic winds along the surrounding hill‐slopes in the morning.…”
Section: Observationssupporting
confidence: 75%
“…Observation of a high peak in ionization rate at about 0600 LT in our radon measurements (Figure ) strongly indicates such downward advection of radon along the hill‐slopes at the measuring site. Supporting such a transport are earlier observations of peaks in ion concentration and electrical conductivity (Dhanorkar and Kamra, ) and radon concentration (Kamsali et al , ) in the early morning hours at the Atmospheric Electricity Observatory, located ∼100 m from this site which also reported similar accumulations of ions and radon and were explained by a similar transport mechanism.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Outdoors, radon will accumulate more in stable atmospheric conditions, so one might expect higher concentrations overnight, when stability is generally higher, with a corresponding increase in ionization, and a decrease after sunrise, as observed by Kamsali et al . []. This also explains the inverse relationship between wind speed and ion concentration, as greater mixing within the boundary layer lowers outdoor radon concentration and ionization rate.…”
Section: Resultsmentioning
confidence: 95%
“…The ion-aerosol model used in this study is shown in Fig. 1, whereas the details of this model for surface level conductivity near to the earth's surface under enhanced aerosol conditions is described by Nagaraja et al [6] and variation of small ions by Nagaraja et al [7]. The two types of  for the attachment of positive and negative ions with the neutral aerosols are considered to be equal.…”
Section: Ion-aerosol Modelmentioning
confidence: 99%